2021
DOI: 10.3390/agronomy11122370
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation with Wastewater and K Fertilization Ensure the Yield and Quality of Coloured Cotton in a Semiarid Climate

Abstract: Treated domestic sewage (TDS) can contribute to plant nutrition and improve crop production. However, there are no data for its use in coloured cotton under a deficit or excess irrigation in combination with potassium fertilization rates (KRs), mainly under semiarid tropical conditions. The research was conducted using a randomized complete block design in a factorial scheme (5 × 5, irrigation regimes vs. potassium rates), plus an additional treatment as the control ((5 × 5) + 1). The treatments consisted of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Moreover, Soeda et al (2005) indicated that deficit water may change the direction of the metabolism process by accelerating the sucrose translocation from leaves to seeds. These results are similar to those obtained by Tsonevet et al (2011), Luo et al (2016), Abd El-Hafeez and Abd El-Gayed (2019) and Lima et al (2021).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Soeda et al (2005) indicated that deficit water may change the direction of the metabolism process by accelerating the sucrose translocation from leaves to seeds. These results are similar to those obtained by Tsonevet et al (2011), Luo et al (2016), Abd El-Hafeez and Abd El-Gayed (2019) and Lima et al (2021).…”
Section: Discussionsupporting
confidence: 92%
“…The controlled application of treated domestic wastewater for irrigation, even with a deliberate water deficit, can play a crucial role in a strategy aimed at conserving fresh water and reducing fertilizer usage. Moreover, it has the potential to boost profit margins in cotton production within tropical semi-arid regions [66]. The most favorable cotton yield, water use efficiency, and potassium use efficiency were achieved when irrigation was conducted at 75% of the crop's evapotranspiration (ETC) or as full irrigation (100% of ETC), especially when combined with a moderate increase in potassium fertilization.…”
Section: Impact Of Nitrogen Fertilizationmentioning
confidence: 99%